2016
DOI: 10.1111/plb.12445
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and sources of variation in pollen deposition and pollen tube formation in flowers of the endemic monoecious shrub Cnidoscolus souzae (Euphorbiaceae)

Abstract: Pollen deposition and pollen tube formation are key components of angiosperm reproduction but intraspecific variation in these has rarely been quantified. Documenting and partitioning (populations, plants and flowers) natural variation in these two aspects of plant reproduction can help uncover spatial mosaics of reproductive success and underlying causes. In this study, we assess variation in pollen deposition and pollen tube formation for the endemic monoecious shrub Cnidoscolus souzae throughout its distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 56 publications
0
13
3
Order By: Relevance
“…Associations between floral traits, HP reception or donation and network properties are variable and even contradictory [3,26,27]. In general, stigma size, flower symmetry and floral size increase the likelihood and intensity of HP reception [3,27,28]. Short styles have been suggested to increase or decrease HP susceptibility [1,4,27].…”
Section: Introductionmentioning
confidence: 99%
“…Associations between floral traits, HP reception or donation and network properties are variable and even contradictory [3,26,27]. In general, stigma size, flower symmetry and floral size increase the likelihood and intensity of HP reception [3,27,28]. Short styles have been suggested to increase or decrease HP susceptibility [1,4,27].…”
Section: Introductionmentioning
confidence: 99%
“…Given that the study species are closely related, this high phylogenetic relatedness may at least partially explain why pollen-pistil incompatibility was the weakest pre-zygotic barrier. Moreover, similarities between the study species in terms of flower morphology and floral biology (Arceo-Gómez et al, 2016;Munguía-Rosas & Jácome-Flores, 2020) could explain why other pre-pollination, pre-zygotic barriers, such as pollinator differentiation (RI: 0.38-0.50), were also relatively weak in this pair of Cnidoscolus species. Thus, our findings have added to the known exceptions (e.g., Costa et al, 2007;Jewell et al, 2012;Johnson et al, 2015;Liao et al, 2019) to the previously depicted pattern regarding the greater strength exhibited by pre-zygotic barriers (Baack et al, 2015;Lowry et al, 2008).…”
Section: Discussionmentioning
confidence: 90%
“…Cnidoscolus souzae is a narrow endemic species, and its entire coarse-grained distribution range is fully embedded within the wider distribution range of C. aconitifolius (Arceo-Gómez et al, 2016;Ross-Ibarra & Molina-Cruz, 2002; Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor (1961) discovered an empirical law in ecology, which links the variance of the population for a species in a habitat area to its corresponding mean by a power-law relationship. This scaling relationship has been expanded from population density and widely observed in ecology (e.g., Cohen et al, 2013;Taylor, 2019), such as pollination success in a shrub species at Mexico's Yucatan Peninsula (Arceo-Gómez et al, 2016). Our recent studies indicated that some plants followed Taylor's law in their growth traits (Chen et al, 2017;Chen, 2020;Chen & Chen, 2020), but it was not tested in pollen shedding.…”
Section: Data Processing and Methodsmentioning
confidence: 99%